Moderasi Beragama Sebagai Strategi Pencegahan Radikalisme di Lembaga Pendidikan Islam: Penelitian - Rina Setyaningsih; Setiawan, Devi; Prabowo, Dibyo; Mayasari, Laila; Julaila, Masdinar; Muzaim (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Religious radicalism has become a serious challenge in the field of education, particularly within Islamic educational institutions. Religious moderation emerges as an alternative paradigm to balance religious understanding that is tolerant, inclusive, and respectful of differences. This article aims to analyze the implementation of religious moderation as a prevention strategy against radicalism in Islamic educational institutions. The research method employed is a literature study by examining various sources related to the concepts of religious moderation, radicalism, and Islamic education. The findings indicate that Islamic educational institutions play a crucial role in internalizing the values of religious moderation through curriculum design, educators’ role modeling, the habituation of a culture of tolerance, and the utilization of digital technology. The implementation of religious moderation has proven effective in curbing the spread of radical ideologies and in shaping young generations with religious.